Mengungkap Transparansi Dan Akuntabilitas Pengelolaan Keuangan Pada Organisasi Sekaa Suka Duka Bharata Dalam Ranah Kearifan Lokal Menyama Braya - I Putu Aryasa; Lucy Sri Musmini (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
Sekaa suka duka is one of the non-legal social organizations in the village of Pakraman that aims to help each member when they have customary and religious activities (Hinduism) both related to situation of happy and sadness. Sekaa suka duka Bharata is one of the sekaa in Bungkulan Village, Sawan District, Buleleng Regency, which was founded in 1990 and has the most members among the sekaa, which is 172 members. The unique phenomenon of this sekaa is that all financial management is only carried out by prajuru sekaa (committee) without being separated from the role of local wisdom of menyama braya which is the key to the harmony of Sekaa suka duka Bharata. This background that makes sekaa suka duka Bharata is interested to be studied to know 1) the background of the formation of sekaa suka duka Bharata, 2) the financial management system in sekaa suka duka Bharata 3) implementation of local wisdom menyama braya in the daily action of the accountability principles and transparency in financial management like sekaa suka duka Bharata. This research was conducted using qualitative methods. Data obtained through in-depth interviews, observation, and documentation study. The data is then analyzed by data reduction, data presentation, and drawing conclusions based on a predetermined theory. The results of this study indicate that; 1) The background of suka duka Bharata was based on shared interests and goals. 2) The financial management system of sekaa suka duka Bharata is managed by prajuru sekaa who are inseparable from local wisdom of menyama braya. 3) Accountability and transparency in financial management carried out by prajuru sekaa have been carried out as they should without leaving the meaning of local wisdom in menyama braya.